2012
DOI: 10.1192/pb.bp.111.036616
|View full text |Cite
|
Sign up to set email alerts
|

Perception of unmet needs and association with benzodiazepine misuse among patients on a methadone maintenance treatment programme

Abstract: Aims and methodTo examine patients' perceptions of unmet needs during methadone maintenance treatment (MMT), and to explore the relationship between co-occurring benzodiazepine misuse and severity of needs. A cross-sectional survey was carried out at an MMT programme in Dublin, Ireland. All patients were invited to participate on a voluntary basis. Of the 191 eligible patients, 107 agreed to participate and completed the Camberwell Assessment of Need questionnaire.ResultsUnmet needs for substance misuse treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Analyses of 2008-2014 NSDUH data found that adults with OUD had a rate of combined sedative/tranquilizer misuse that was approximately 20 times greater than the U.S. general population, with 43% reporting pastyear sedative/tranquilizer misuse (Votaw et al, 2019). Benzodiazepine misuse is often even more prevalent among people in treatment for OUD; past-month estimates range from 7-73%, with a majority (67%) of studies reviewed reporting rates greater than 40% (Apantaku-Olajide et al, 2012;Bleich et al, 2002;Darke et al, 1993Darke et al, , 1994bEiroa-Orosa et al, 2010;Franklyn et al, 2017;Gelkopf et al, 1999;Ghitza et al, 2008;Gilchrist et al, 2006;McHugh et al, 2017;Metzger et al, 1991;Millson et al, 2006;Moitra et al, 2013;Naji et al, 2016;Peles et al, 2009Peles et al, , 2010Stein et al, 2017b;Stein et al, 2016;Vogel et al, 2013;Wu et al, 2010).…”
Section: Substancementioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of 2008-2014 NSDUH data found that adults with OUD had a rate of combined sedative/tranquilizer misuse that was approximately 20 times greater than the U.S. general population, with 43% reporting pastyear sedative/tranquilizer misuse (Votaw et al, 2019). Benzodiazepine misuse is often even more prevalent among people in treatment for OUD; past-month estimates range from 7-73%, with a majority (67%) of studies reviewed reporting rates greater than 40% (Apantaku-Olajide et al, 2012;Bleich et al, 2002;Darke et al, 1993Darke et al, , 1994bEiroa-Orosa et al, 2010;Franklyn et al, 2017;Gelkopf et al, 1999;Ghitza et al, 2008;Gilchrist et al, 2006;McHugh et al, 2017;Metzger et al, 1991;Millson et al, 2006;Moitra et al, 2013;Naji et al, 2016;Peles et al, 2009Peles et al, , 2010Stein et al, 2017b;Stein et al, 2016;Vogel et al, 2013;Wu et al, 2010).…”
Section: Substancementioning
confidence: 99%
“…General population samples in the U.S. (adults and young adults/adolescents) Lower levels of education, lower income, unemployment, and being unmarried were associated with benzodiazepine misuse (Arterberry et al, 2016;Becker et al, 2007;Blanco et al, 2018;Goodwin and Hasin, 2002;Huang et al, 2006;McCabe et al, 2018;Schepis et al, 2018a) Adults with opioid misuse/SUDs/injection drug use Lower levels of education, homelessness, unemployment, and/or being unmarried were associated with benzodiazepine misuse (Apantaku-Olajide et al, 2012;Backmund et al, 2005;Bleich et al, 1999;Bleich et al, 2002;Darke et al, 1992;Eiroa-Orosa et al, 2010;Lavie et al, 2009) Those with benzodiazepine misuse were less likely to be homeless, more likely to be married and employed, and/or had greater levels of education (Ickowicz et al, 2015;Malcolm et al, 1993;Moitra et al, 2013) No association between homelessness, marital status, employment status, level of education, income, and benzodiazepine misuse (Bouvier et al, 2018;Brands et al, 2008;…”
Section: Highlightsmentioning
confidence: 99%
“…When conducting a user-centered evaluation of OMT services, several indicators or assessment areas should be considered: a) user expectations and objectives for the treatment or intervention, 15 , 16 b) patient beliefs or opinions about medication (primarily methadone or buprenorphine), 17 – 21 c) user appraisal of the relational dynamic with intervention providers 22 – 24 and the degree of perceived participation in decision-making, 25 , 26 as well as patient preferences for a participatory or deferential role, 27 , 28 d) indicators of user-perceived quality, 29 e) client perception of unmet needs, 30 , 31 and f) level of satisfaction with treatment. 8 , 11 , 25 , 32 …”
Section: Towards a More User-centered Approach To Program Evaluationmentioning
confidence: 99%
“…Despite these fi ndings, client-level data suggest that many client needs are unmet (Apantaku-Olajide et al, 2012;Machlan et al, 2005;Pringle et al, 2006). To date, there has been less organizational-level research on how client characteristics are associated with the provision of wraparound services in SUD treatment programs across the United States.…”
mentioning
confidence: 94%